Detecting long‐term losses at the plant community level – arable fields in Germany revisited. Issue 3 (15th March 2015) - Meyer, Stefan; Bergmeier, Erwin; Becker, Thomas; Wesche, Karsten; Krause, Benjamin; Leuschner, Christoph; Schwabe‐Kratochwil, Angelika
Abstract Question The intensification of crop cultivation in much of Europe since the mid‐20th century has greatly increased crop yields but caused dramatic biodiversity losses in arable fields. We investigated the extent of these losses at the level of plant community types. Location Ten areas in central Germany with different soil/climate conditions and various arable plant communities. Methods We compiled historical surveys of arable fields in the 1950s/early 1960s before the onset of pervasive agricultural industrialization, and in 2009 revisited 392 arable fields. Historical and recent data were compared with supervised manual classification, detrended correspondence analysis (DCA) and ANOVA. Results Ten out of 16 plant communities at association rank observed in fields in the 1950s/1960s were not recorded again. The proportion of relevés assignable at association level decreased from 75% to 5%, while the proportion of relevés assignable only at higher syntaxon level or not assignable at all had increased from 2% to 75%. The impoverishment of vegetation was slightly less pronounced at field margins, where around one quarter of the recent relevés could be assigned to associations. Present arable plant communities in the region are species‐poor and consist chiefly of common, often herbicide‐tolerant, generalist species, with no clear preference for cereal vs root crops, autumn‐ vs spring‐sown crops or base‐rich vs base‐poor soils. Conclusion Our new approach using phytosociological syntaxa and a semi‐permanent plot design enabled us to quantify biodiversity losses at the community type level. The currently used set of phytosociological associations is inadequate to represent present‐day arable plant assemblages. The concept of residual plant communities provides a useful methodological supplement.